Xerostomia, salivary characteristics and gland volumes following intensity‐modulated radiotherapy for nasopharyngeal carcinoma: a two‐year follow up. (24th April 2018) - Sim, CPC; Soong, YL; Pang, EPP; Lim, C; Walker, GD; Manton, DJ; Reynolds, EC; Wee, JTS
Abstract: Background: To evaluate changes in xerostomia status, salivary characteristics and gland volumes 2 years following radiotherapy in nasopharyngeal carcinoma patients. Methods: Xerostomia scores, salivary flow rates, pH and buffering capacity were measured at pre‐radiotherapy, mid‐radiotherapy, 2 weeks, 3 months and 2 years post‐radiotherapy. Salivary gland volumes and their correlation with radiation dose were also assessed. Results: Mean radiation dose to oral cavity, parotid and submandibular glands (SMG) was 44.5, 65.0 and 38.6 Gy respectively. Parotid and SMG volumes decreased 33% at 3 months post‐radiotherapy; volumes at 2 years post‐radiotherapy were 84% and 51% of pre‐radiotherapy levels, respectively. Correlations were observed between parotid gland volume per cent reduction and its radiation dose and between resting salivary flow rate reduction and post‐radiotherapy/pre‐radiotherapy SMG volume ratio. Salivary flow rates and resting saliva pH remained significantly low at 2 years post‐radiotherapy (both flow rates, P = 0.001; resting saliva pH, P = 0.005). Similarly, xerostomia scores remained significantly higher compared with pre‐radiotherapy levels. Conclusions: Submandibular gland volumetric shrinkage persisted 2 years after radiotherapy. Xerostomia scores remained significantly higher, and salivary flow rates and resting saliva pH remained significantly lower, suggesting that study participants were still at risk for hyposalivation‐related oral diseases.